The Impact of COVID-19 Pandemic in Children With Cancer: A Report From Saudi Arabia. (December 2020) - Alshahrani, Mohammad; Elyamany, Ghaleb; Sedick, Qanita; Ibrahim, Walid; Mohamed, Amal; Othman, Mohamed; Al Thibani, Nour; Alsuhaibani, Omar; Al Amro, Mohamed; Gharawi, Ali; Al Sharif, Omar; Elborai, Yasser; et al.
In January 2020, the WHO declared the novel coronavirus (2019-nCoV) outbreak as a public health emergency of international concern. Due to the rapid spread of 2019-nCoV, all countries started preventive and precautionary measures to prevent COVID-19 infection spread. These measures limited the population mobility and services provided, which subsequently Impact of on children with cancer and cancer care delivery in the many health centers in Saudi Arabia. We did a cross-sectional study to assess the impact of this outbreak on children with cancer concerning all aspects of life including medical services provided, the specific precautions to prevent spread in cancer patients, mental, psychological effects, and its effect on the quality of life. We collected 204 responses during a survey that assessed the impact on the treatment of cancer children at a tertiary institution during the COVID-19 pandemic. The majority of patients were receiving ongoing chemotherapy for leukemia/lymphoma. The majority of these patients (60.5%) reported a delay in treatment received due to hospital cancellation of appointments due to the pandemic. Although the majority of patients in our cohort complained of delayed treatment, fortunately, none of the delays led to fatalities. In the context of global lockdowns and physical distancing to help flatten the COVID-19 curve, telemedicine has proved fundamental to keeping patients and their healthcare providers connected and safe. Children also faced multiple other difficulties such as psychosocial issues during the COVID-19 pandemic. Our long-term goals are to develop new programs that will enable children with cancer to emerge successfully during a pandemic.